The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jclepro.2021.126333
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on food waste behaviour of young people

Abstract: The aim of this research is to analyse the way young people perceive the food waste process, as well as the determinants and the impact of the COVID-19 pandemic on the responsible behaviour of young people towards food waste. The research design involves a study on a sample of 375 students from Romanian universities and the development and validation of a model using SEM-PLS. Our findings show that the impact of the COVID-19 pandemic has led to more people exhibiting food waste reduction behaviour, an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
93
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 72 publications
7
93
2
Order By: Relevance
“…No clear differences were found in relation to sociodemographic variables. This is contrary to other studies suggesting relevant differences between age groups in the case of external shocks, such as climate change (Andor et al, 2018;Burlea-Schiopoiu et al, 2021). In this sense, it seems that the impact of the pandemic on the assessment of certain preferences and beliefs was not decisive to change them.…”
Section: Discussioncontrasting
confidence: 91%
“…No clear differences were found in relation to sociodemographic variables. This is contrary to other studies suggesting relevant differences between age groups in the case of external shocks, such as climate change (Andor et al, 2018;Burlea-Schiopoiu et al, 2021). In this sense, it seems that the impact of the pandemic on the assessment of certain preferences and beliefs was not decisive to change them.…”
Section: Discussioncontrasting
confidence: 91%
“…Young consumers are more concerned about the economic aspects than the health and environmental concerns of food waste [ 37 ]. Furthermore, the young consumer may not optimize their food consumption as they are not familiar with the reusing of leftover food [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that COVID-19 (the disease itself as well as measures implemented to control its spread) has negatively impacted the global food system in a multitude of ways [2,13]. Broadly, factors leading to or causing food insecurity linked to the current pandemic include but are not limited to the reduction in food production/availability/ demand [14,15], increased food waste, especially at harvest time or in markets [16][17][18], and labour shortages in the various sectors of the food system, as well as job and income losses [19,20]. As the pandemic brought additional workload for women in family care and formal and informal healthcare [13], it also added an additional pressure on their capacity in all pillars of food security as they were disproportionately affected by the socioeconomic fallout (job and livelihood losses) [8].…”
Section: Introductionmentioning
confidence: 99%